Advanced UV Spectrophotometry-Classical Least Squares Determination of Paracetamol, Phenylpropanolamine HCl, and Chlorpheniramine Maleate in Tablet Dosage Form - Tarigan, Rida Evalina; Sajida, Nurul; Surbakti, Chemayanti (Publisher Cv. Inara, 2024)
This study aims to develop and validate an advanced UV spectrophotometry- Classical Least Squares (CLS) for the simultaneous determination of Paracetamol (PA), Phenylpropanolamine HCl (PH), and Chlorpheniramine Maleate (CH) in tablet dosage form. The method involves the preparation of standard solutions of the three compounds across their respective concentration ranges 3-9 µg/mL for PA, 170-512 µg/mL for PH, and 7-19 µg/mL for CH. The CLS spectrophotometry UV method was applied to these spectra to construct calibration, which were then used to predict the concentrations of PA, PH, and CH in tablet dosage form. Validation of the method demonstrated excellent linearity, precision, and accuracy, with recovery rates of 99.26% for PA, 100.06% for PH, and 99.41% for CH. Sensitivity analysis revealed Limits of Detection (LOD) of 0.10 µg/mL for PA, 1.20 µg/mL for PH, and 0.30 µg/mL for CH, and Limits of Quantification (LOQ) of 0,30 µg/mL for PA, 4.00 µg/mL for PH, and 1.50 µg/mL for CH. The method’s robustness and reliability make it an excellent choice for routine quality control of these compounds in pharmaceutical tablet formulations.